Predomina la raza 2 del patogeno del anublo de halo en cultivos de frijol del Oriente Antioqueno - Tamayo Molano, Pablo J.; Pastor Corrales, Marcial A. (1991)
A survey of Pseudomonas syringae race 2 in bean crops was conducted to determine its distribution in eastern Antioquia, Colombia. Race 2 currently predominates in the bean-growing area of this region as well as in other parts of Colombia. Crops are monitored to restrict the dissemination of P. syringae. (CIAT)